Ironie, Erotik und Techno-Politik: Cyberfeminismus als Virus in der neuen Weltunordnung? - Weber, Jutta (Die Philosophin. Forum für feministische Theorie und Philosophie, 12. Jg. H. 24, Dez. 2001)

Selbstorganisation als ‚little invisible hands‘: Artificial Life und die wunderbare Ordnung einer undurchschaubaren Welt - Weber, Jutta (Hand. Körper – Medium – Technik)

`Der schmale Grat´ oder: Gibt es einen gen(d)eration gap im Kontext feministischer Netzwerke? – Ein pädagogisch-philosophisches Streitgespräch - Weber, Jutta; Maurer, Susanne (metis. Zeitschrift für kritische Frauenforschung und feministische Praxis, 10. Jg., H.19)

Die Verständlichkeit von frühreformatorischen Flugschriften. Eine Studie zu kommunikationswirksamen Faktoren der Textgestaltung - Schuster, Britt-Marie

Falcon, Cornélie - Grotjahn, Rebecca (Die Musik in Geschichte und Gegenwart. Bd. 6)

Customer-Oriented Systems Design through Virtual Prototyps - Flake, Stephan; Geiger, Christian; Müller, Wolfgang; Ruf, Jürgen (Proceedings of IEEE KMN 2001)
Rapid prototyping based on 3D models is well accepted for several applications. This article addresses the application of animated virtual 3D prototypes for the development of computer-based systems supporting early collaboration of the system designer with the external customer. Our methodology seamlessly integrates illustration through 3D animation with the main tasks of computer-based real-time systems development, i.e., implementation and verification. The approach is outlined by the example of the design of a flexible manufacturing system.
Keywords: Virtual prototyping; Animation; Collaboration; System analysis and design; Feedback; Application software; Power system modeling; Handicapped aids; Process design; Contracts

Advanced Infrastructure for PAN-European Collaborative Engineering - Bauer, M.; Eikerling, Heinz-Josef; Müller, Wolfgang; Pawlak, A.; Siekierska, K.; Soderberg, D.; Warzee, X.
This article presents challenges, visions, and solutions for a true Pan- European collaborative engineering infrastructure that is a target of the IST project E-COLLEG. The consortium aims at the definition of a transparent infrastructure that will enable engineers from various domains to collaborate during the design of complex heterogeneous systems. In this context, we introduce an advanced collaborative infrastructure (ACI). ACI covers dynamic Tool Registration and Management Services (TRMS) for distance-spanning, tool integration and administration, as well as open interfaces for XML-based data exchange. TRMS will constitute a backbone for E-COLLEG-related pan-European collaborative research and engineering studies by fostering a combination of most recent Plug- and-Play techniques employing agent-based communication based on XML- oriented integration technologies. This new enabling technology for collaborative engineering is validated in two application scenarios.

The Simulation Semantics of SystemC - Müller, Wolfgang; Ruf, Jürgen; Hoffmann, D. W.; Gerlach, Joachim; Kropf, Thomas; Rosenstiehl, W. (Proceedings of the Design, Automation, and Test in Europe (DATE’01))
We present a rigorous but transparent semantics definition of SystemC that covers method, thread, and clocked thread behavior as well as their interaction with the simulation kernel process. The semantics includes watching statements, signal assignment, and wait statements as they are introduced in SystemC V1.O. We present our definition in form of distributed Abstract State Machines (ASMs) rules reflecting the view given in the SystemC User's Manual and the reference implementation. We mainly see our formal semantics as a concise, unambiguous, high-level specification for SystemC-based implementations and for standardization. Additionally, it can be used as a sound basis to investigate SystemC interoperability with Verilog and VHDL.
Keywords: Yarn; Formal verification; Kernel; Hardware design languages; Electronic design automation and methodology; Algebra; Computational modeling; Logic functions; Computer languages; Clocks

Real-Time Model Checking for the Analysis of flexible Manufacturing Systems - Flake, Stephan; Müller, Wolfgang; Pape, U.; Ruf, Jürgen (Proceedings of ISI 2001)

A Language for the Rapid Prototyping of Mobile Evolving Agents - Müller, Wolfgang; Meyer, A.; Zabel, Henning (Proceedings of the 34th Annual Hawaii International Conference on System Sciences)
This article presents SAL, a general purpose scripting language for the rapid development of distributed software agents seamlessly embedded in a visual environment. Integrated facilities for dynamic visualization provide sample but powerful means for debugging and domain-oriented animation. SAL agents are arranged on a set of 2D worksheets which can be distributed over different machines. An agent's program is defined by the means of a table specifying a set of state transition rules with a condition and a sequence of actions each. Beyond basic computation and communication, actions can dynamically modify the agent's depiction, its program, and spawn arbitrary processes. A couple of examples demonstrate SAL's applicability in various domains like electronic systems design and process management.
Keywords: software prototyping; distributed programming; authoring languages; software agents; program visualisation; parallel languages

Security Concepts for Agent-Based Systems - Lehrenfeld, Georg; Müller, Wolfgang; Tellmann, Rainer (Proceedings of SCASE 01)

Performance and dynamics of a RF MEMS switch - Plotz, F; Michaelis, S; Fattinger, G; Aigner, R; Noé, Reinhold (TRANSDUCERS ‘01: EUROSENSORS XV, DIGEST OF TECHNICAL PAPERS, VOLS 1 AND 2)

Arbeit “in Kontrasten” – Künstler- und Vaterschaft in Theodor Storms Novelle Eine Malerarbeit - Morrien, Rita (Schriften der Theodor-Storm-Gesellschaft)

Männer – Blicke, Frauen – Körper. Die Inszenierung des weiblichen Körpers in der Literatur der Bürgerzeit - Morrien, Rita (SCHRIFT/zeichen – Zeitschrift für literatur [kunst] religion)

Origin of reciprocal circular birefringence observed in X-cut, Z-propagation LiNbO3 polarization transformers - Bhandare, S; Noé, Reinhold; Sandel, D (APPLIED PHYSICS B-LASERS AND OPTICS)

Crosstalk detection schemes for polarization division multiplex transmission - Noé, Reinhold; Hinz, S; Sandel, D; Wust, F (JOURNAL OF LIGHTWAVE TECHNOLOGY)

Optimization of TE-TM mode converters on X-cut, Y-propagation LiNbO3 used for PMD compensation - Bhandare, S; Noé, Reinhold (APPLIED PHYSICS B-LASERS AND OPTICS)

PMD compensation in a 2x40Gbit/s, 212km, CS-RZ polarization multiplexed transmission experiment - Sandel, D; Wust, F; Mirvoda, V; Noé, Reinhold (ECOC’01: 27TH EUROPEAN CONFERENCE ON OPTICAL COMMUNICATION, VOLS 1-6)

150fs online PMD detection within 5 mu s - Noé, Reinhold; Sandel, D; Mirvoda, V; Hinz, S; Wust, F (ECOC’01: 27TH EUROPEAN CONFERENCE ON OPTICAL COMMUNICATION, VOLS 1-6)

Optical amplifier performance in digital optical communication systems - Noé, Reinhold (ELECTRICAL ENGINEERING)

Interference detection enabling 2 x 20Gbit/s RZ polarisation division multiplex transmission - Hinz, S; Sandel, D; Wust, F; Noé, Reinhold (ELECTRONICS LETTERS)

Tolerance of bandwidth-efficient optical multilevel modulation schemes against polarization mode dispersion - Hinz, S; Noé, Reinhold; Sandel, D; Wust, F (ELECTRICAL ENGINEERING)

kT/C noise: Covariance matrix calculation of instationary noise in time-varying systems - Noé, Reinhold (AEU-INTERNATIONAL JOURNAL OF ELECTRONICS AND COMMUNICATIONS)

PMD tolerance of polarization division multiplex transmission using return-to-zero coding - Hinz, S; Sandel, D; Wust, F; Noé, Reinhold (OPTICS EXPRESS)

A low-voltage torsional actuator for application in RF-microswitches - Plotz, R; Michaelis, S; Aigner, R; Timme, HJ; Binder, J; Noé, Reinhold (SENSORS AND ACTUATORS A-PHYSICAL)

Optical amplifier performance in digital optical communication systems - Noé, Reinhold (ELECTRICAL ENGINEERING)

84fs PMD detection sensitivity in 2 x 40 Gbit/s RZ polarisation multiplex transmission experiment - Sandel, D; Noé, Reinhold; Mirvoda, V; Hinz, S; Wust, F (ELECTRONICS LETTERS)

Tolerance of bandwidth-efficient optical multilevel modulation schemes against polarization mode dispersion - Hinz, S; Noé, Reinhold; Sandel, D; Wust, F (ELECTRICAL ENGINEERING)

Interference detection enabling 2 x 20Gbit/s RZ polarisation division multiplex transmission - Hinz, S; Sandel, D; Wust, F; Noé, Reinhold (ELECTRONICS LETTERS)

kT/C noise: Covariance matrix calculation of instationary noise in time-varying systems - Noé, Reinhold (AEU-INTERNATIONAL JOURNAL OF ELECTRONICS AND COMMUNICATIONS)

PMD tolerance of polarization division multiplex transmission using return-to-zero coding - Hinz, S; Sandel, D; Wust, F; Noé, Reinhold (OPTICS EXPRESS)

A low-voltage torsional actuator for application in RF-microswitches - Plotz, R; Michaelis, S; Aigner, R; Timme, HJ; Binder, J; Noé, Reinhold (SENSORS AND ACTUATORS A-PHYSICAL)

84fs PMD detection sensitivity in 2 x 40 Gbit/s RZ polarisation multiplex transmission experiment - Sandel, D; Noé, Reinhold; Mirvoda, V; Hinz, S; Wust, F (ELECTRONICS LETTERS)

Kunst-Macht-Gewalt. Der ästhetische Ort der Aggressivität - Öhlschläger, Claudia (Arbitrium)

Spezifikation von Echtzeiteigenschaften mit OCL für eine MFERT-basierte Fallstudie - Flake, Stephan; Müller, Wolfgang
Die Object Constraint Language (OCL) wurde entwickelt, um Modellierer bei der Spe- zifikation von Modelleigenschaften im Kontext gegebener UML Diagramme zu un- terst ̈utzen [3]. Jedoch ist es leider nicht m ̈oglich, Eigenschaften, die das dynamische Verhalten betreffen, mit der derzeitigen Version von OCL auszudr ̈ucken. Wir pr ̈asentieren eine Erweiterung von OCL Version 1.4 zur Spezifikation von zu- standsbasierten, zeitbehafteten Eigenschaften. Obwohl OCL und unsere Erweiterung in erster Linie im Rahmen der UML entwickelt worden sind, ist es auch m ̈oglich, mit dieser Sprache Eigenschaften f ̈ur andere objektbasierte Formalismen zu beschrei- ben. Wir veranschaulichen dies anhand einer Anwendung bei der Modellpr ̈ufungsspe- zifikation in Verbindung mit MFERT, einer praxisrelevanten Notation, die im Projekt GRASP zur Modellierung von Produktionsabl ̈aufen eingesetzt wird.

Generation of Interactive Visual Interfaces for Resource Management - Dangberg, Andreas; Müller, Wolfgang (Proceedings of ISI 2001)
This paper introduces the VIVID (Visual Interactive VIew Development) framework for generation and customization of advanced visual interactive environments for resource manipulation in databases. The framework covers the definition of symbols, their mapping to database objects, specification of spatial relationships among them, layout assignment as well as the definition of drag&drop-based user interactions.

Sinn und Sinnlichkeit. Der weibliche Körper in der deutschen Literatur der Bürgerzeit - Morrien, Rita

Chirality in Liquid Crystals: Introduction - Bahr, C.; Kitzerow, Heinz-Siegfried (Chirality in Liquid Crystals)

Twist Grain Boundary Phases - Kitzerow, Heinz-Siegfried (Chirality in Liquid Crystals)

Theologische Musik? Neue Musik? Messiaen, die evangelische Kirchenmusik und die Moderne - Grotjahn, Rebecca (Le Sacre. Musik – Ritus – Religiosität; Biennale Neue Musik Hannover 2001)

Die Soubrette Antonie Held und ihr Kontrakt mit dem Hoftheater zu Hannover - Grotjahn, Rebecca (Viva voce)

Angelica Catalani – Das Bild der Diva - Grotjahn, Rebecca (Viva voce)

Low-rank approximation of improper complex random vectors - Schreier, Peter J.; Scharf, Louis L. (Proc. 35th\ Asilomar Conf.\ Signals Syst.\ Computers)
In reduced-rank signal processing for radar, sonar, and digital communications, we seek the right tradeoff between model bias and model variance for reconstructing signals from noisy data. Here, we extend the classical theory by considering the low-rank approximation of complex random vectors, which may or may not be proper. We show that, in general, widely linear approximation is superior to strictly linear approximation, unless the vector to be approximated is proper, in which case the optimum procedure is strictly linear. We analyze the case where the approximated random vector becomes proper in its internal coordinate system. This class of random vector, which we call generalized proper, possesses qualities similar to proper random vectors.

A Database for Field Extensions of the Rationals - Klüners, Jürgen; Malle, Gunter (LMS Journal of Computation and Mathematics)
This paper announces the creation of a database for number fields. It describes the contents and the methods of access, indicates the origin of the polynomials, and formulates the aims of this collection of fields.
Keywords: Computational Theory and Mathematics; General Mathematics

Soziale Selbstorganisation im informationsgesellschaftlichen Kapitalismus (Social Self-Organization and Informational Capitalism) - Fuchs, Christian

Mesoporous Aluminophosphate Molecular Sieves Synthesized under Nonaqueous Conditions - Tiemann, Michael; Schulz, Marcus; Jäger, Christian; Fröba, Michael (Chemistry of Materials)
Long-chain n-alkylamine surfactants have been used as structure-directing agents in the synthesis of mesoporous aluminophosphates by a highly cooperative formation mechanism in an alcoholic system. Small amounts of water in the synthesis mixture play a significant role in the hydrolysis of the aluminum precursor (Al[OiPr]3) and are important for the quality of the mesostructured products. The materials exhibit disordered mesostructures, the stability and structural order of which can be improved by a postsynthetic thermal treatment. The products are then stable enough for the removal of the surfactant molecules by acidic solvent extraction, yielding surface areas up to 690 m2/g.

Mesostructured Aluminophosphates Synthesized with Supramolecular Structure Directors - Tiemann, Michael; Fröba, Michael (Chemistry of Materials)
Over the past few years a growing number of scientists have dedicated their attention to the synthesis of mesostructured aluminophosphates following the concept of supramolecular structure direction. Their research has produced a large variety of synthetic approaches and yielded materials with various structural properties. Today a substantial number of publications have accumulated; this short review provides a general summary of the literature with the aim to display the opportunities for future work.

Coulomb correlation signatures in the excitonic optical nonlinearities of semiconductors - Meier, Torsten; Koch, S.W. (Ultrafast Physical Processes in Semiconductors)
This chapter focuses on the carrier interaction effects—that is, the many-body Coulomb correlations and their influence on band-gap semiconductor optical nonlinearities. The near band-gap semiconductor response is determined by the optical interaction with the resonant or near resonant material polarization that may result in the excitation of carriers (electron–hole pairs) and/or transient coherent nonlinearities. The microscopic analysis of these effects requires the investigation of the relevant quasi-particles and their interactions. Whereas the basic occurrence of a blue shift can be motivated already based on a simple two-level model, a more detailed understanding of the optical Stark effect in semiconductors requires a microscopic modeling of the relevant bands as well as the inclusion of the many-body Coulomb interaction. Compensations among the first- and higher-order Coulomb terms at the spectral positions of the exciton are obtained in the differential absorption induced by incoherent occupations.

Spectral signatures of χ(5) processes in four-wave mixing of homogeneously broadened excitons - Meier, Torsten; Langbein, W.; Koch, S.W.; Hvam, J.M. (Journal of the Optical Society of America B)
The influence of fifth-order coherences on the spectrally resolved four-wave mixing response of predominantly homogeneously broadened quasi-two-dimensional excitons is studied. Fifth-order signatures are discussed as a function of spectral position and excitation polarization. An exciton–biexciton beating for positive delay times is the dominant effect, which is pronounced at the exciton–biexciton transition for collinearly polarized excitation and at the exciton transition for cross-linearly polarized excitation. For negative delay times and collinearly polarized excitation a pronounced exciton–biexciton beating at the exciton resonance is observed that is vanishing for long negative delays owing to the faster dephasing in the two-exciton continuum compared with the bound biexciton state. These results are in qualitative agreement with microscopic model calculations that include the coherent dynamics of one- and two-exciton resonances up to the fifth order in the optical field.

Linear and nonlinear optical properties of semiconductor nanorings with magnetic field and disorder-Influence on excitons and biexcitons - Meier, Torsten; Thomas, P.; Koch, S.W. (The European Physical Journal B - Condensed Matter and Complex Systems)
Linear and nonlinear optical absorption spectra are studied theoretically for semiconductor nanorings penetrated by a magnetic field. Due to the Aharanov-Bohm effect the spectral position as well as the oscillator strength of the exciton change periodically as function of the magnetic flux enclosed by the ring. In the nonlinear differential absorption spectra it is found that the magnetic field strongly modifies Coulomb many-body correlations. In particular, the magnetic-field-induced increase of the exciton binding energy is accompanied by a decrease of the biexciton binding energy. The persistence of these effects in the presence of energetic disorder is analyzed.